Social Movements: Scientific Research Scenarios in Non-Formal Education: Educación no formal de y con los Movimientos Sociales - Pérez Pérez, Isabel; Arroyo Agamez, Nasly (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The purpose of this article has to do with the analysis of social movements as scenarios of scientific research in non-formal education, the methodological process is part of a type of qualitative research, with the complement of an exploratory-descriptive approach and the information collection instrument is a documentary or bibliographic review. The result of the research shows that social movements are promoters of intercultural and inclusive educational strategies and styles that tend to achieve social development and community empowerment.